BEHAVIOR OF PROSTAGLANDIN E2 IN THE TUMOR MICROENVIRONMENT AND ITS IMPACT ON DENDRITIC CELLS: AN INTEGRATIVE REVIEW - Espanhol, Fernando Araújo; Vieira, Julia Hailer; Michelin, Márcia Antoniazi (Acta Biologica Brasiliensia, 2024)
This integrative review provides an in-depth analysis of the influence of prostaglandin E2 on the intratumoral environment, highlighting its association with forms of immune evasion. The studies reviewed reveal that the presence, behavior, and overexpression of PGE2 are crucial in shaping the tumor microenvironment, emphasizing the need for a more detailed understanding of these interactions. Several studies have emphasized the importance of investigating agents capable of modulating cytokines and chemokines in the tumor microenvironment and using immunotherapy as a promising approach to treat specific immunometabolic conditions. These alternatives aim to strengthen the host immune system against tumor cells, representing a hopeful strategy to overcome the immunosuppression barriers associated with molecules such as prostaglandin E2. Therefore, this review highlights the complexity of the interactions between PGE2, dendritic cells, and cancer, indicating promising avenues for future research and more targeted and effective therapeutic interventions.